Toward High‐Dimensional Single‐Cell Analysis of Graphene Oxide Biological Impact: Tracking on Immune Cells by Single‐Cell Mass Cytometry. Issue 21 (27th April 2020) - Orecchioni, Marco; Bordoni, Valentina; Fuoco, Claudia; Reina, Giacomo; Lin, Hazel; Zoccheddu, Martina; Yilmazer, Acelya; Zavan, Barbara; Cesareni, Gianni; Bedognetti, Davide; Bianco, Alberto; Delogu, Lucia Gemma
Abstract: Considering the potential exposure to graphene, the most investigated nanomaterial, the assessment of the impact on human health has become an urgent need. The deep understanding of nanomaterial safety is today possible by high‐throughput single‐cell technologies. Single‐cell mass cytometry (cytometry by time‐of flight, CyTOF) shows an unparalleled ability to phenotypically and functionally profile complex cellular systems, in particular related to the immune system, as recently also proved for graphene impact. The next challenge is to track the graphene distribution at the single‐cell level. Therefore, graphene oxide (GO) is functionalized with AgInS2 nanocrystals (GO–In), allowing to trace GO immune–cell interactions via the indium ( 115 In) channel. Indium is specifically chosen to avoid overlaps with the commercial panels (>30 immune markers). As a proof of concept, the GO–In CyTOF tracking is performed at the single‐cell level on blood immune subpopulations, showing the GO interaction with monocytes and B cells, therefore guiding future immune studies. The proposed approach can be applied not only to the immune safety assessment of the multitude of graphene physical and chemical parameters, but also for graphene applications in neuroscience. Moreover, this approach can be translated to other 2D emerging materials and will likely advance the understanding of their toxicology. Abstract : The study of the underlying immune system functional responses to graphene oxide at a high‐dimensional single‐cell level is unrestricted by the inherent mass limitation of carbon‐based nanomaterials in single‐cell mass cytometry. This work provides an approach that can able to track graphene oxide interaction with the complexity of the immune system.